KEPATUHAN HUKUM KONSULTAN PAJAK KOTA MEDAN TERHADAP KEWAJIBAN PENDAFTARAN BPJS KETENAGAKERJAAN: FAKTOR PENYEBAB DAN KONSEKUENSI HUKUM - Brahmana, Herman; Rumapea, Mazmur Septian; Siburian, Sukses Marhasak Panungkunan; Kuara, Glenessa; Sunjoyo, Alexandra Martha Santoso; Irawan, Agus (jurnal.unprimdn.ac.id, 2023)
BPJS Ketenagakerjaan is a public legal entity formed to conduct Social Security programs in the Employment Sector. Participation is mandatory for workers and companies. A tax consultant also acts as an employee and is not exempt from such BPJS obligations. The public often does not comply with regulations due to various obstacles, including many Medan Tax Consultants. The problem in this research is how Medan Tax Consultants comply with such BPJS registration, factors that cause compliance or non-compliance, and legal consequences resulting from such non-compliance. The research is located in Medan and is empirical descriptive-analytical. Samples were taken using a purposive sampling technique of 10% out of 172 population. Data sources consist of primary and secondary data. The research was preceded by a library study and thennterviews (with questionnaires). Then, qualitative analysis is applied, and conclusions are drawn using the deductive approach. The results show that Medan Tax Consultant’s compliance level still needs to be higher. The main factor causing compliance is to get rid of sanctions, while the leadingause of non-compliance is the need to understand the BPJS regulations. The effectiveness of such BPJS regulations among Medan City Tax Consultants is still low and requires continuous supervision from BPJS.